A Hybrid Numerical Method to Cure Numerical Shock Instability (Communications in Computational Physics, 2010)
In this note, we propose a new method to cure numerical shock instabilityby hybriding different numerical fluxes in the two-dimensional Euler equations. Theidea of this method is to combine a "full-wave" Riemann solver and a "less-wave" Riemannsolver, which uses a special modified weight based on the difference in velocityvectors. It is also found that such blending does not need to be implemented in allequations of the Euler system. We point out that the proposed method is easily extendedto other "full-wave" fluxes that suffer from shock instability. Some benchmarkproblems are presented to validate the proposed method.